Exploring Pediatric Neuroblastoma: A Comprehensive Analysis of Adrenal and Nonadrenal Tumor Characteristics in the United States - AlWawi, Ghaith; Alrefai, Mohammad Omar; Al-Wawi, Mohd Zaki; Qasim, Asma; Hammami, M. Bakri (Avicenna Journal of Medicine, 2025)
Neuroblastoma (NB) is an aggressive malignant tumor arising from a primitive neural crest origin. While the significance of tumor location in survival outcomes is recognized, it remains inadequately explored. This study provides a comprehensive analysis of the survival and characteristics of pediatric adrenal and nonadrenal NBs in the United States.A retrospective analysis of pediatric primary NB between 1975 and 2016 was conducted using the Surveillance, Epidemiology, and End Results (SEER) database. Univariate and multivariate regression analyses were used to determine prognostic variables.A total of 4,554 patients were included, comprising 52% males (n = 2,385) and 79.2% Caucasians (n = 3,569). The median age of the patients was one year (range: 0–19 years). In all, 44.4% (n = 1,996) of the patients had adrenal NB and 55.6% (n = 2,496) patients had nonadrenal NB. Adrenal NB was significantly more prevalent among males and those presenting at a younger age (p < 0.001). Adrenal NB was more likely to have a higher grade and distant metastasis at diagnosis (p < 0.001). Nonadrenal NB, female sex, surgical resection, and later year of diagnosis were associated with improved survival (p < 0.001).This study highlights important factors that are helpful for prognostication of NB patients in the United States. Tailored approaches considering tumor site are crucial for effective management of NB.
Keywords: neuroblastoma; adrenal; nonadrenal; survival outcomes; prognostic factors; population-based study; pediatric oncology